Phaseolin diversity in cultivated common bean from the Caribbean Diversidad de faseolinas en frijol común cultivado del Caribe - Hidalgo Rigoberto; Blair Mathew; Pantoja Wilfredo (Acta Agronómica)
In this study, 180 genotypes of cultivated Phaseolus vulgaris from the Caribbean were evaluated with the phaseolin marker. All the accessions belonged to the germplasm collection of the International Center for Tropical Agriculture (CIAT). Beans from Cuba were mostly S phaseolin (68.0 %) type, with small seed size, red and black seed color and type II or type III growth habit. These were followed by beans with T phaseolin (20.0 %) and finally by those with B, CH and Sd phaseolin. In Haiti, the most common phaseolin was T (48.1%), the majority of which were large seeded bush beans, mostly of the red mottled seed color class. Many of the remaining accessions were S phaseolin (42.6%) and had small black seed, although a few had B, Sb and Sd phaseolin (4.6, 2.8 and 1.9% of genotypes, respectively). In Puerto Rico, T phaseolin was in the majority with 57.1%, most of these with large red or red mottled seed. S phaseolin was represented by 42.9 % of landraces some of which had small yellow, black or white seed. In the Dominican Republic, the T phaseolin was very abundant (85.7%) the majority of which were medium to large seeded bush beans all of which were red mottled. A smaller proportion of Dominican landraces had S and B phaseolin (9.5% and 4.8% respectively). Finally, in Jamaica, T phaseolin was found for 40.0 % of the landraces, B phaseolin was equally common and 20% of the landraces had S phaseolin although this was based on a small sample of genotypes. The phaseolin patterns indicated the prevalence of both Andean and Mesoamerican beans in the Caribbean. Se evaluó el tipo de faseolina en 180 accesiones cultivadas de Phaseolus vulgaris del Caribe de la colección del Centro Internacional de Agricultura Tropical (CIAT). En fríjoles de Cuba (25 accesiones) predominó el tipo S (68%, semilla pequeña, roja o negra y hábito de crecimiento de tipos II y III), seguidos por fríjoles con faseolina T (20 %) y con un bajo porcentaje los tipos B, CH y Sd. En Haití (108 accesiones) las faseolinas más comunes fueron T (48.1%, semilla grande, rojo moteado y hábito arbustivo) y S (42.6%, semilla pequeña, negra), y unas pocas mostraron faseolinas B, Sb y Sd. En los fríjoles de Puerto Rico (21 accesiones) las faseolinas más comunes fueron T (57.14%, semilla grande, rojo moteada) y S (42.86%, semilla pequeña amarilla, negra o blanca). En los de República Dominicana (21 accesiones) abundó el tipo T (85.7%, semilla grande o mediana rojomoteada). En los fríjoles de Jamaica (5) predominaron las faseolinas T y B (40% de cada una). Los patrones de faseolina indicaron la prevalencia tanto de fríjoles Mesoamericanos como Andinos.